State of the art: Targeting microsatellite instability in gastrointestinal cancers - Mencel, Justin; Alves, Anneke; Angelis, Vasileios; Gerlinger, Marco; Starling, Naureen (Critical reviews in oncology/hematology, 2024)
DNA mismatch repair (MMR) deficiency and the associated microsatellite instability (MSI) phenotype has become a subject of enormous interest in recent years due to the demonstrated efficacy of immune checkpoint inhibitors (ICI) in advanced tumours. Assessing MSI in patients with gastrointestinal tract (GI) cancers is useful to exclude Lynch syndrome, but also to predict benefit for ICI. Following review of the relevant literature, this review article aims to outline the clinicopathologic spectrum of MSI and mismatch repair deficiency (dMMR) in the GI tract, hepatobiliary system and pancreas and discuss the therapeutic consideration in this disease. •Defects in DNA mismatch repair can be seen in several GI tumours.•Tissue based immunohistochemistry and next generation sequencing are used to detect microsatellite instability.•Evidence to support the use of immune checkpoint inhibitors in GI cancers including in both early and late stage disease is evolving.